A High‐Resolution View of the Coordination Environment in a Paramagnetic Metalloprotein from its Magnetic Properties. Issue 27 (26th May 2021) - Ravera, Enrico; Gigli, Lucia; Suturina, Elizaveta A.; Calderone, Vito; Fragai, Marco; Parigi, Giacomo; Luchinat, Claudio
Abstract: Metalloproteins constitute a significant fraction of the proteome of all organisms and their characterization is critical for both basic sciences and biomedical applications. A large portion of metalloproteins bind paramagnetic metal ions, and paramagnetic NMR spectroscopy has been widely used in their structural characterization. However, the signals of nuclei in the immediate vicinity of the metal center are often broadened beyond detection. In this work, we show that it is possible to determine the coordination environment of the paramagnetic metal in the protein at a resolution inaccessible to other techniques. Taking the structure of a diamagnetic analogue as a starting point, a geometry optimization is carried out by fitting the pseudocontact shifts obtained from first principles quantum chemical calculations to the experimental ones. Abstract : A close look from a distance: Pseudocontact shifts depend on the magnetic susceptibility of the metal center, which in turn depends on the coordination geometry. We exploit these dependencies to obtain a detailed view of metal coordination in a metalloprotein.